QUALITY OF SERVICE TO CUSTOMER SATISFACTION IN CLEANING SERVICE - Natsir Mallawi, Muhammad; Andi Wahyu Rezki; Abdul Gaffar (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2021)
The quality of cleaning services is at the core of the University Politeknik cleaning services. Customer satisfaction often uses assessment methods to determine the quality of cleaning services. Customer satisfaction depends on customer expectations and quality awareness factors. This study uses a qualitative approach. The data collection method used is survey research that takes data using questionnaires, observations and interviews.